Investigation of test performance of the dual reminder A-Not A (DR A-Not A) in comparison to 3-AFC for discriminating samples of drinking water. (October 2019) - Mun, Ji-Won; Kim, Min-A; Sim, Hye-Min; Lee, Hye-Seong
Highlights: Dual reminder A-Not A(DR A-Not A) designed to detect off-sensory characteristics. This method was tested on practicality of quality management of drinking water. For using DR A-Not A with two odd stimuli, the optimal β-strategy was adopted. Performance of unspecified DR A-Not A was comparable to that of specified 3-AFC. Dual reminder scheme found to be an efficient practice to utilize SDT A-Not A model. Abstract: Although the relative performance of sensory discrimination methods is well theorized in Thurstonian modeling and signal detection theory (SDT), empirical research is needed to investigate how such theorized models could be validated in complex sensory testing situations of food and beverages. This paper presents a practical procedure to utilize the existing SDT-based A-Not A sensory discrimination model based on a beta-strategy for detecting the off-sensory quality of samples of drinking water and validates the model for effective and efficient sensory quality management of food and beverages. Dual reminder A-Not A (DR A-Not A) using two tastings of the reference stimulus before evaluating every test stimulus is proposed as the optimal test procedure because it uses more sensitive test sequences and facilitates subjects' familiarization with the standard quality of the reference. To test the performance of DR A-Not A, 3-AFC, which also uses three stimuli and is the recommended method for detecting odor or taste stimuli by ASTM, was used as a control method. In Experiment 1, 98 subjects each performed both DR A-Not A and 3-AFC. Based on these results, only sensitive subjects were selected for the next experiment, in which they were divided into two equally well performing groups. In Experiment 2, each group performed either DR A-Not A or 3-AFC over three repeated sessions. The results confirmed that the A-Not A beta-strategy was adopted for DR A-Not A and that its test performance was improved over replications. These results suggest that although DR A-Not A is an unspecified difference test method and does not use a forced-choice task, embedding the familiarization procedure for the reference renders it an effective sensory difference method for the sensory quality management of drinking water.